Accounting Interpretation of Cross-border Mergers in the Czech Republic Based on Czech Accounting Standards - Jana Skálová; Tomáš Podškubka (European Financial and Accounting Journal, 2009)
The paper deals with cross-border mergers that may be performed either out of or into the Czech Republic and focuses on the accounting and tax aspects of these transactions. Attention was also paid to the most important legal requirements imposed on merger projects and the net assets valuations. The Directive 2005/56/EC brought in new possibilities of business transformations across the EU member states' borders. Income tax advantages that may be gained in cross-border mergers were implemented by virtue of the Directive 90/434/EEC. It may be difficult to meet stringent requirements that are conditional upon enjoyment of the neutral tax treatment.
Keywords: G34; H25; M41; 650; Cross-border mergers; Czech Republic; Decisive Day; Merger Project; Opening balance sheet; Valuation Report